ANALYSIS OF THE PREVALENCE OF SELF-MEDICATION BY STUDENTS AT A PRIVATE UNIVERSITY IN THE CITY OF ANÁPOLIS, GOIÁS (CIPEEX, 2026)
The undergraduate period is characterized by high demands and stress, increasing students vulnerability. In this context, the use of stimulant medications and supplements, particularly through self-medication, has become common among students in the fields of health, humanities, and exact sciences, aiming to alleviate symptoms of physical and mental fatigue. This scenario can lead to negative consequences, such as addiction, overdose, and adverse effects of the medications, thus requiring greater attention from professionals and educators regarding the issue. Therefore, the main objective of this study was to analyze the use of both prescribed and non-prescribed medications by students from the fields of Health, Humanities, and Exact Sciences at a private university in Anápolis, Goiás. This is a cross-sectional study that analyzed 454 students from UniEVANGÉLICA, in the Anápolis campus, selected from the courses with the highest number of students in each field. The data were collected via an online or printed questionnaire and analyzed using the chi-square test (p
Keywords: Medicine; Self-medication; Students; Goiás